Linking Eye Design with Host Symbiont Relationships in Pontoniine Shrimps (Crustacea, Decapoda, Palaemonidae) - Dobson, Nicola C. (Public Library of Science, 2014)
Symbiosis is prevalent in the marine environment with many studies examining the effects of such interactions between host and symbiont. Pontoniine shrimps are a group whose ecology is characterised by symbiotic interactions. This investigation examines the gross morphology of Pontoniinae compound eyes and superficial optical parameters with reference to their symbiotic relationship or lifestyle category; free-living, ectosymbiont, endosymbiont (bivalves) or endosymbiont (non-bivalves). The eye morphologies of free-living and ectosymbiotic species are very similar, yet differ from both forms of endosymbiotic species. Endosymbionts have significantly smaller and simpler eyes with larger facets and bigger interommatidial angles and eye parameters for increased sensitivity levels. However bivalve endosymbionts form an intermediary group between non-bivalve endosymbionts and ectosymbionts as a result of their more active lifestyle. The accessory eye or “nebenauge”, although of uncertain function, commonly occurs in free-living Pontoniinae species but rarely in endosymbionts apart from in more primitive species. The variation in morphology reflects tensions between functional requirements and ecological pressures that have strongly influenced eye design in Pontoniinae.